Pelestarian Desa Hilinawalo Mazino di Kepulauan Nias sebagai destinasi wisata (ARTEKS : Jurnal Teknik Arsitektur, 2019)
Hilinawalo Mazino Village conservation in Nias Islands as tourism destination Nias is an island located West of Sumatra Island, located in North Sumatra Province. Hilinawalo Mazino Village is a village located in Mazino District, South Nias Regency which has an area of 8.5 square kilometers. Hilinawalo Mazino village has many traditional Nias houses, but after the 2005 earthquake and damage due to the maintenance of residents, it changed Hilinawalo Mazino Village to add some of their traditional houses. The purpose of this studio is to find ways to preserve to maintain the state and sustainability of Hilinawalo Mazino Village as a sustainable tourism destination in the Nias Islands. Methods of collecting data by observation, secondary data surveys and interviews. Methods of analyzing data by processing survey results obtained with 4 principles of Tourism Village Development Guidelines. In conclusion, the way to preserve Hilinawalo Mazino Village as a tourist destination is realized with these 4 principles.© 2019 Anugerah Septiaman Harefa
Keywords: Conservation; Development; Tourism